SKINCARE LEARNING YOUTH EDUCATION PROGRAM FOR KNOWLEDGE IMPROVEMENT AT SMA NEGERI 1 SUBOH SITUBONDO - Ika Puspita Dewi; Diana Holidah; Mochammad Amrun Hidayat (UPT Penerbitan Universitas Jember, 2022)
Teenagers' lack of knowledge of cosmetics causes the risk of using dangerous or illegal products. Students at SMA Negeri 1 Suboh Situbondo have never received special material regarding the selection and use of beauty products. The outcome of this educational program is to increase the knowledge of SMA Negeri 1 Suboh students about how to use and choose the right and safe skincare. This program is carried out by offline method at SMA Negeri 1 Suboh Situbondo and online method with the Zoom Meeting. The materials given to students are various teenage skin problems, introduction to skincare ingredients, and choosing the right skincare. The results of the survey related to the skin characteristics of the participants showed that most of the skin types owned by students of SMA Negeri 1 Suboh were oily (38.09%), with most of them having skin problems (79.37%), and the majority problem was acne (42.68%), while 79.37% of participants had used skincare. The results of the post-test showed that the average score of the participants was 88.57, which indicates most of the participants had understood the materials given. This program has succeeded in providing information about the correct, appropriate, and safe use of skincare to the students of SMA Negeri 1 Suboh Situbondo. Keywords: knowledge, skincare, SMA Negeri 1 Suboh Situbondo, teenager